Analysis of Financial Performance Using the Du Pont System at Pt Darya-Varia Laboratoria TBK for the Period 2023-2025 - Afsha Harnia; Aisyah Nurhalizah Arifin; Rizky Natasya; Siti Khairunnisa; Zahira Naswa Ramadani; Heriyati Chrisna (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
This study was conducted to examine the financial performance of PT Darya-Varia Laboratoria using the DuPont system over a three-year period, as the company is listed on the Indonesia Stock Exchange. The entire data set for this analysis includes all available financial statements of PT Darya-Varia Laboratoria for the study period. The sample consists of the statements of financial position (balance sheets) and income statements of PT Darya-Varia Laboratoria Tbk obtained from the Indonesia Stock Exchange (IDX) for the years 2023–2025. Data collection was conducted through documentation and literature review, utilizing secondary data derived from the company’s financial statements and various supporting references. Data analysis employed a comparative analysis method, which involves comparing financial statements from one period to another to identify changes, both in rupiah terms and as percentages.The variables analyzed in this study include Net Profit Margin (NPM), Total Asset Turnover (TATO), and Return on Investment (ROI) based on the Du Pont approach. The variables were measured using a ratio scale because the data used are numerical and can be compared quantitatively. Next, the data were analyzed using descriptive methods with a quantitative approach to describe the company’s financial performance during the study period. The research findings show that PT Darya-Varia Laboratoria Tbk’s Net Profit Margin (NPM) declined from 7.74% in 2023 to 7.35% in 2025. Total Asset Turnover (TATO) fluctuated from 0.93 times to 0.97 times and then fell to 0.95 times. The Equity Multiplier (EM) increased from 1.45 times to 1.59 times, while Return on Equity (ROE) rose from 10.61% to 11.09%. These results indicate that the company’s overall financial performance improved, as reflected by the rise in ROE, despite the decline in the net profit margin. The increase in ROE was driven by more efficient use of assets and increased corporate leverage.